Open data for promotion of transparency and innovation: the case of UFRN - Júnior, Gibeon Soares de Aquino; Jacob, Elias; Henrique, Gusttavo; Guerethes, Jean; Silva, Renan de Oliveira (iSys - Journal of Information Systems, 2019)
The recent rise of open data movements in Brazil is noticeable. It was allowed mainly by advances in legislation on transparency and integrity in the Public Sector. The adoption of open data by public institutions, aligned with a policy of support and encouragement to the consumption of them, provides innumerable benefits to society and the institution itself. In this sense, this article aims at presenting how UFRN’s adopted strategy contributed to promoting satisfactory transparency in public administration while has fostered an ecosystem of innovation.